A simple model for simulation of reservoir stratification. Issue 4 (4th July 2019) - Noori, Roohollah; Asadi, Nasibeh; Deng, Zhiqiang
ABSTRACT: This paper presents a reduced-order model (ROM) for simulation of thermal stratification in reservoirs by combining the CE-QAUL-W2 (W2) and the proper orthogonal decomposition (POD) models. The Karkheh Dam Reservoir (KDR) was used as a case study where the water temperature (WT) simulated with W2 model provided the necessary information for the development of ROM. The main outputs of ROM, containing spatio-temporal patterns of WT variation in the KDR, were produced with the POD model. WT profiles of the KDR, simulated with both ROM and W2, were presented and compared. W2 calibration and verification results revealed a good agreement between the simulated vertical WT profiles and measured ones in the reservoir. The mean absolute errors (MAEs) for calibration and verification of WT profiles were 0.71 and 0.67°C, respectively. The results also indicated a good agreement between the WT profiles simulated with the W2 and the ROM developed using the first 10 out of 3425 modes, as evidenced by a small absolute error (<0.5°C). The agreement demonstrated that the performance of the developed ROM was comparable with that of the existing W2 while the new ROM was much simpler in model structure and thus easier to use than the W2 model.